2005
DOI: 10.1143/jjap.44.5137
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization Process of Secondary Crystal Nodules from Individual Nuclei in Electrodeposition

Abstract: Using nonequilibrium fluctuations in electrodeposition, the self-organization process of secondary crystal nodules from individual nuclei was examined. As a result, it was concluded that electrodeposition can be described by two types of fluctuation, i.e., symmetrical and asymmetrical fluctuations; the former yields three-dimensional (3D) nuclei, whereas the latter yields two-dimensional (2D) nuclei that determine the spatial distribution of the 3D nuclei. The complex self-organization of these two types of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Such effects have been quite extensively documented in the literature, mainly for copper, 8,17,44 and it has been suggested that they are somehow associated with convection generated by the Lorentz force. 45, 46 Aogaki 47 has proposed that the field effect on two-dimensional nucleation is related to spontaneous concentration fluctuations in the double layer, and the effect on three-dimensional nucleation depends on fluctuations in the diffusion layer.…”
Section: B Normal Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such effects have been quite extensively documented in the literature, mainly for copper, 8,17,44 and it has been suggested that they are somehow associated with convection generated by the Lorentz force. 45, 46 Aogaki 47 has proposed that the field effect on two-dimensional nucleation is related to spontaneous concentration fluctuations in the double layer, and the effect on three-dimensional nucleation depends on fluctuations in the diffusion layer.…”
Section: B Normal Patternsmentioning
confidence: 99%
“…The MHD effect, and its analog on a small length scale, the micro-MHD effect 17 are responsible for many of the influences that a magnetic field can have in electrochemistry, including the rate of electrodeposition of metals, 3,5,7 deposit morphology, 8 hydrogen production, 10,11 corrosion, [12][13][14][15][16] and rest potential. 18 The hydrodynamic conditions in any experiment are characterized by a set of dimensionless numbers whose significance in a laboratory electrochemical cell is summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…These two types of nucleation come from different nonequilibrium fluctuations. (10,17); one is asymmetrical fluctuation, which arises from an electrochemical reaction in an electrical double layer. As shown in this figure, this fluctuation one-sidedly changes from an electrostatic-equilibrium state toward a cathodic reaction side, controlling 2D-nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the schematic diagram of an electrical potential distribution in the double layer for the electrodeposition without any specific adsorption, where the overpotentials of the double layer are negative. As shown in this figure, let's assume that a minute 2D nucleus is accidentally formed in the diffuse layer of the double layer (10,17). Since the potential gradient in the diffuse layer is positive, at the top of the nucleus, the double-layer overpotential decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation